(untitled) (XXI Century. Spanish Literature and Culture, 2008)
El mismo mar de todos los veranos is one of the most significant texts of the Spanish postmodern novel. Throughout the novel, Esther Tusquets proposes a representation of the new and complex conscience, which results in a text that is difficult to read. … first a pragmatic approximation of the text and second, a semantic one. This analysis will serve to test the borders between modern and postmodern narratives in what we can call a novel of the Spanish transition to democracy that was produced at the end of the 70´s and the beginning of the 80´s, and will also interpret the representation of the conscience proposed by Tusquets under the consideation of the schizophrenic conscience formulated by Deleuze and Guattari in the book Capitalismo et schizophénie. L’Anti-Œdipe.